Comparing the Effects of Sleep and Rest on Memory Consolidation - Tucker MA (Dove Medical Press, 2020)
Matthew A Tucker,1 Graelyn B Humiston,2 Theodore Summer,2 Erin Wamsley2 1University of South Carolina School of Medicine, Department of Biomedical Sciences, Greenville, SC, USA; 2Furman University, Department of Psychology and Program in Neuroscience, Greenville, SC, USACorrespondence: Matthew A TuckerUniversity of South Carolina School of Medicine, Department of Biomedical Sciences, Health Sciences Administration Building (HSAB) 248, 701 Grove Road, Greenville, SC 29605, USATel +1 864-455-8945Email matucker@greenvillemed.sc.eduIntroduction: There is ample evidence that overnight sleep and daytime naps benefit memory retention, compared to comparable amounts of active wakefulness. Yet recent evidence also suggests that a period of post-training rest (eg, quiet wakefulness with eyes closed) provides a similar memory benefit compared to wake. However, the relative benefits of sleep vs quiet waking rest on memory remain poorly understood. Here, we assessed the extent to which sleep provides a unique memory benefit, above and beyond that conferred by quiet waking rest.Methods: In a sample of healthy undergraduate students (N=83), we tested the effect of 30 mins of post-learning sleep, rest, or active wake on concept learning (dot pattern classification) and declarative memory (word pair associates) across a 4-hr daytime training-retest interval.Results and Conclusions: Contrary to our hypotheses, we found no differences in performance between the three conditions for either task. The findings are interpreted with reference to methodological considerations including the length of the experimental interval, the nature of the tasks used, and challenges inherent in creating experimental conditions that can be executed by participants.Keywords: rest, sleep, memory consolidation, concept learning, declarative memory